User Satisfaction of Accounting Information System Using Multiple Linear Regression Analysis - Ni Putu Lisa Ernawatiningsih; I Putu Edy Arizona (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2021)
The development of information systems is closely related to accounting which is useful for the operations of every organization. Almost every company uses information system to carry out their activities today. The information system will continue to develop and getting more advanced. This study aims to test and obtain empirical evidence of influence of information system quality, service quality, perceived usefulness, and top management support on user satisfaction of accounting information systems at Sakajaja Makmur Abadi Company. The sample in this study was 38 employees determining based on the side purposive method. The analytical tool using multiple linear regression analysis. The result showed variables of information system quality, service quality, perceived usefulness has a positive effect on user satisfaction of accounting information systems, while the variable top management support has no effect on user satisfaction of accounting information systems.